Study of operation of spool hydraulic control unit that transmits reduced pressure signal to control hydraulic distributors, control cylinders, parameters of axial piston pumps and hydraulic motors - E. R. Butakova; А. А. Sekacheva; А. S. Noskov (Омский научный вестник: Серия "Авиационно-ракетное и энергетическое машиностроение")
The article discusses the test results of three modernized hydraulic control units. In the course of the experiments, the nodes are refined with subsequent refinement tests. As a result, of the research, the following results are obtained: a characteristic of the dependence of the differential pressure on the flow rate, a dependence of the reduction pressure on the angle of the handle, pressure drops in the working bends of the control unit, etc. The analysis of the results and comparison with theoretical calculation shows that there are three main types of adjustment characteristics: parallel theoretical —with laminar flow, three — zone and quadratic — with turbulent mode.